Microbial biotechnology : progress and trends - Darvishi Harzevili, Farshad, Ed. Chen, Hongzhang (CRC Press, 2014)
Incorporates the Experiences of World-Class ResearchersMicrobial Biotechnology: Progress and Trends offers a theoretical take on topics that relate to microbial biotechnology. The text uses the ""novel experimental experiences"" of various contributors from around the world-designed as case studies-to highlight relevant topics, issues, and recent developments surrounding this highly interdisciplinary field. It factors in metagenomics and microbial biofuels production, and incorporates major contributions from a wide range of disciplines that include microbiology, biochemistry, genetics, mole.